A single, triple chaotic cryptography using chaos in digital filter and its own comparison to des and triple des - Pich, Reatrey; Chivapreecha, Sorawat; Prabnasak, Jaruwit (My University, 2018)
The Data Encryption Standard (DES) of the multimedia cryptography possesses the weak point of key conducting that is why it reaches to the triple form of DES. However, the triple DES obtains the better characteristic to secure the protection of data to against the attacks, it still contains an extremely inappropriate performance (speed) and efficiency in doing so. This paper provides the effective performance and the results of a single and triple chaotic cryptography using chaos in digital filter, compare to DES and triple DES. This comparison has been made pair-to-pair of single structure respectively to the triple form. Finally the implementation aspects of a single chaotic cryptography using chaos in digital filter can stand efficiently as better performance speed with the small complexity algorithm, points out the resemblances to DES and triple DES with the similar security confirmation results without reaching to the triple form of the structure. Simulation has been conducted using Matlab simulation with the input of grayscale image.
Keywords: Chaos in Digital Filter; Cryptography; DES; Triple DES